2022
DOI: 10.1021/acsami.2c17331
|View full text |Cite
|
Sign up to set email alerts
|

Polarity-Reversible Te/WSe2 van der Waals Heterodiode for a Logic Rectifier and Polarized Short-Wave Infrared Photodetector

Abstract: As a p-type elemental material with high carrier mobility, superior ambient stability, and anisotropic crystal structure, emerging two-dimensional (2D) tellurium (Te) has been considered a successor to black phosphorus for developing infrared-related optoelectronics. Nevertheless, the lack of a scalable thickness engineering strategy remains an obstacle to unleashing its full potential. Te-based electronics with logic functions are also less explored. Herein, we propose a novel wet-chemical thinning method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…When a sinusoidal signal is input, the output can get the positive or negative portions, and the polarity of the half‐wave rectifier can be switched because of the gate‐modulation polarity switching in our designed WTe 2 /WS 2 diode in Figure a. [ 15 ] Figure 3b shows the schematic diagram of the polarity switchable logic half‐wave rectifier. Figure 3c shows the output V out curve of a rectifier with an input sinusoidal signal at a peak‐to‐peak voltage (the difference between the maximum positive input voltage and the maximum negative input voltage) of 4 V at the frequency of 16 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a sinusoidal signal is input, the output can get the positive or negative portions, and the polarity of the half‐wave rectifier can be switched because of the gate‐modulation polarity switching in our designed WTe 2 /WS 2 diode in Figure a. [ 15 ] Figure 3b shows the schematic diagram of the polarity switchable logic half‐wave rectifier. Figure 3c shows the output V out curve of a rectifier with an input sinusoidal signal at a peak‐to‐peak voltage (the difference between the maximum positive input voltage and the maximum negative input voltage) of 4 V at the frequency of 16 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ] Fortunately, 2D van der Waals (vdW) heterostructure obtained by artificial stacking or epitaxial growth is an efficient strategy for improving electrical and optoelectronic performance, without considering the lattice matching constraint. [ 13 ] Most importantly, various reconfigurable phenomena based on 2D vdW heterostructures can be discovered such as anti‐ambipolar behavior, [ 14 ] dynamic polarity conduction, [ 15 ] gate‐modulated rectifying behavior, [ 16 ] nonvolatile storage and memory, [ 17 ] bidirectional photoresponse, [ 18 ] etc. As a 2D reconfigurable phototransistor (RPT), the sign of the photocurrent can be modulated by bias, gate voltage (V g ), and wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers started to focus on the construction of the heterojunction of Te. Attempts have been made to form Te van der Waals heterojunctions utilizing 2D materials (such as MoS 2 , MoSe 2 , and graphene), Si and Ge etc., [26,[54][55][56][57][58] whereas suffering a slow photoresponse. Overall, the Te photodetectors mainly relied on single crystals or nanosheets and adopted the photoconductive (PC) or field-effect transistor (FET) structures, which are not conducive to CMOS integration.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al demonstrated a broadband and sensitive photodetector based on Te/WSe 2 vdWH, covering a range of 650-1550 nm. [31] Meanwhile, Cao et al reported a photodetection based on Te/In 2 S 3 heterojunction, achieving a responsivity of 303 mA/W. [32] Despite these advances, there are still challenges to overcome in realizing high-sensitivity self-powered light detection without relying on an external power supply.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated a broadband and sensitive photodetector based on Te/WSe 2 vdWH, covering a range of 650–1550 nm. [ 31 ] Meanwhile, Cao et al. reported a photodetection based on Te/In 2 S 3 heterojunction, achieving a responsivity of 303 mA/W.…”
Section: Introductionmentioning
confidence: 99%